2010
DOI: 10.1007/s00296-010-1611-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in erythrocytes from patients with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation. It has been suggested that the level of reactive oxygen species (ROS) in patients with RA is higher than in healthy subjects. The aim of the present study was to investigate the level of the lipid peroxidation, antioxidant enzyme activities (CAT, SOD, GSH-Px), level of the –SH groups and GSH and Na+K+ ATPase activity in erythrocytes from patients with RA. There are no significant differences in CAT and GSH-Px activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 21 publications
8
34
0
1
Order By: Relevance
“…Level of the lipid peroxidation is significantly higher in the patients with RA than in the control group and it is in agreement with most studies Sarban et al [29]. On the basis of the obtained results and the literature data, it can be concluded that in RA, red blood cells are more susceptible to the influence of free radicals Staroń et al [30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Level of the lipid peroxidation is significantly higher in the patients with RA than in the control group and it is in agreement with most studies Sarban et al [29]. On the basis of the obtained results and the literature data, it can be concluded that in RA, red blood cells are more susceptible to the influence of free radicals Staroń et al [30].…”
Section: Discussionsupporting
confidence: 90%
“…His results confirm increase in oxidative stress in RA patients, while, Staroń et al [30] stated that there is no significant difference between CAT and GSH activities as regarding RA. In Sarban et al [29] study, the concentration of the GSH is about 20% lower in RA patients than in healthy subjects.…”
Section: Discussionmentioning
confidence: 82%
“…It is well known that the serum SH groups levels are modified in many diseases, including obesity, indicating that SH groups content is a useful biochemical marker of "in vivo" oxido-reduction reactions (16). Membrane SH groups are liable to be modified by different oxidants or alkylating agents, increasing their membrane permeability to different ions, such as Ca ++ , which can promote excitotoxicity, by RNS and ROS that lead to lipid peroxidation, increasing the levels of TBARS and decreased concentration of SH groups in membrane proteins (17). Thiol-containing molecules with SH bonds such as glutathione (GSH) suppress oxidative damage and involve the maintenance of the cell redox status.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the article by Staron et al [1] dealing with an association between oxidative stress parameters in erythrocytes and rheumatoid arthritis (RA) patients. The authors have analyzed thiobarbituric acid, total ATPase, Na ?…”
Section: Sirmentioning
confidence: 99%